2012
DOI: 10.1111/j.1445-5994.2011.02711.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B status in migrants and refugees: increasing health burden in Western Australia

Abstract: This study highlights the increasing burden of CHB in Western Australia, from people born in endemic countries, in particular, the direct costs of treatment. It will help to develop strategies that can be tailored to Western Australia with appropriate allocation of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Aberra et al (2017) 12 Aberra et al (2017) 12 Aberra et al (2017) 12 Aberra et al (2017) 12 Al-Naamani et al (2013) 15 Coppola et al (2017) 51 Cotler et al (2009) 52 Cuomo et al (2016) 55 De Vroey et al (2013) 59 Deltenre et al (2012) 60 Ding et al (2013) 63 Fallatah et al (2010) 71 Fung et al (2011) 76 Fung et al (2011) 76 Milosevic et al (2013) 118 Pérez-Molina et al (2011) 129 Spradling et al (2013) 142 Stefos et al (2009) 143 Stroffolini et al (2012) 146 Subramaniam et al (2012) 147 Tedder et al (2013) 152 Vella et al (2012) 158 Widjaja et al (2007) 160 Yuen et al (2009) 169…”
Section: Weight (%) Proportion (95% Ci)mentioning
confidence: 99%
“…Aberra et al (2017) 12 Aberra et al (2017) 12 Aberra et al (2017) 12 Aberra et al (2017) 12 Al-Naamani et al (2013) 15 Coppola et al (2017) 51 Cotler et al (2009) 52 Cuomo et al (2016) 55 De Vroey et al (2013) 59 Deltenre et al (2012) 60 Ding et al (2013) 63 Fallatah et al (2010) 71 Fung et al (2011) 76 Fung et al (2011) 76 Milosevic et al (2013) 118 Pérez-Molina et al (2011) 129 Spradling et al (2013) 142 Stefos et al (2009) 143 Stroffolini et al (2012) 146 Subramaniam et al (2012) 147 Tedder et al (2013) 152 Vella et al (2012) 158 Widjaja et al (2007) 160 Yuen et al (2009) 169…”
Section: Weight (%) Proportion (95% Ci)mentioning
confidence: 99%
“…Asian migrants had a high prevalence of chronic hepatitis B (CHB) than their African counterparts (54.3% vs 36.7%; n = 478); they were at risk of cirrhosis unless treated and increased cost over ten years [ 45 ]. Women born in Afghanistan, Bhutan, Iraq, and Myanmar, had poor maternal health, poor pregnancy care attendance, and late booking of visits [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…high rate of HBV infection, which contributes to the relatively steady prevalence of HBV. 5,54 Reprioritizing health spending to widen the scope for a rapid antiviral treatment to reach populations such as people with CALD backgrounds at high risk of getting infected with HBV is an effective investment strategy for the health system for elimination of HBV. 55 The two major HBV antiviral treatments, such as the use of entecavir and tenofovir, are now off-patent, and generic medications make wider availability more economically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…4 For example, in Western Australia, an increasing trend of HBV-associated referrals was reported and most of them were patients born in Asia (57%) and Africa (35%). 5 Reekie et al 6 reported high prevalence rates of HBV in Australian migrant women born in Cambodia (8.6%), Taiwan (8.1%), Vietnam (7.5%), China (6.8%) and Tonga (6.5%). The high rates of HBV in migrants increase the risk of transmission to other migrants and the local community in the receiving country and shape the epidemiology of HBV in a country.…”
Section: Introductionmentioning
confidence: 99%